2015
DOI: 10.1093/femsec/fiv081
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the genetic and phenotypic diversity among rhizogenicAgrobacteriumbiovar 1 strains infecting solanaceous and cucurbit crops

Abstract: Rhizogenic Agrobacterium biovar 1 strains have been found to cause extensive root proliferation on hydroponically grown Cucurbitaceae and Solanaceae crops, resulting in substantial economic losses. As these agrobacteria live under similar ecological conditions, infecting a limited number of crops, it may be hypothesized that genetic and phenotypic variation among such strains is relatively low. In this study we assessed the phenotypic diversity as well as the phylogenetic and evolutionary relationships of seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(61 citation statements)
references
References 52 publications
1
57
0
3
Order By: Relevance
“…After 24 h of incubation, the diameter of the inhibition visible zones surrounding spotted colonies was recorded using a digital caliper (Tyc et al, 2014; Bosmans et al, 2016b). Experiments were performed for one rhizogenic Agrobacterium biovar 1 strain (ST15.13/097, isolated from tomato; Bosmans et al, 2015), and were independently repeated twice (no replicates within the same experiment).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…After 24 h of incubation, the diameter of the inhibition visible zones surrounding spotted colonies was recorded using a digital caliper (Tyc et al, 2014; Bosmans et al, 2016b). Experiments were performed for one rhizogenic Agrobacterium biovar 1 strain (ST15.13/097, isolated from tomato; Bosmans et al, 2015), and were independently repeated twice (no replicates within the same experiment).…”
Section: Methodsmentioning
confidence: 99%
“…Antagonistic effects were observed as a clear zone of inhibition where growth of the tested bacterium was inhibited (+). −, no inhibition zone observed .b AD, NIOO culture collection, Wageningen, The Netherlands; LMG, Laboratory of Microbiology, Ghent University, Ghent, Belgium; MAFF, NIAS Genebank (National Institute of Agrobiological Sciences), Ibaraki, Japan; NCPPB, National Collection of Plant Pathogenic Bacteria, York, UK; EMI, EPU, EHE, and ST, PME&BIM culture collection, Sint-Katelijne Waver, Belgium .c Agrobacterium biovar 1 strains isolated from Cucurbitaceae (melon, cucumber) and Solanaceae (tomato crops; for more information, see Bosmans et al, 2015) are indicated by green and red circles, respectively .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations